Facial Palsy in Melkersson-Rosenthal Syndrome and Bell's Palsy: Familial History and Recurrence Tendency. (February 2015) - Sun, Baochun; Zhou, Chengyong; Han, Zeli
Objective: The aim of this study was to compare genetic predilection and recurrence tendency between facial palsy in Melkersson-Rosenthal syndrome (MRS) and Bell's palsy Methods: We carried out an investigation on patients with facial palsy in MRS and those with Bell's palsy who visited the outpatient department in our hospital between February 2009 and February 2013. They were asked about familial history and whether it was the first episode, with the results recorded and compared. Results: There were 16 patients with facial palsy in MRS and 860 patients with Bell's palsy involved in the study. Familial history was positive in 5 of 16 patients (31.3%) with facial palsy in MRS and 56 of 860 patients (6.5%) with Bell's palsy ( P < .01). Twelve of 16 cases (75%) with facial palsy in MRS and 88 of 860 cases (10.2%) with Bell's palsy had a history of facial palsy in the past ( P < .01). Conclusion: Compared to Bell's palsy, facial palsy in MRS has an obvious genetic predilection and recurrence tendency.